2010
DOI: 10.1055/s-0029-1245540
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung des Coeruloplasmins für die Differenzialdiagnose neuropsychiatrischer Störungen

Abstract: The blue copper protein ceruloplasmin has been of interest to psychiatrists for decades following Heilmeyer's observation of elevated serum copper levels in schizophrenic patients. Immunoturbidimetry, however, does not yield elevated serum ceruloplasmin concentrations in schizophrenia while ceruloplasmin-related oxidase activity appears to be elevated in patients with schizophrenia and reduced in patients with Alzheimer's disease. Low serum concentrations of immuno-turbidimetrically measured ceruloplasmin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
1
0
1
Order By: Relevance
“…Score plot of the 1 st BE and BPRS canonical variates; dotted line represents the moving median with 5 rows step Our finding of negative correlation of copper (Cu) concentration with total BPRS and negative symptoms was in line with the findings of Wang 1988, Zhai 1990, Luo 1991. It was different to Rahman et al 2009 andConnemann et al 2010 finding that the concentration of copper (Cu) is increased in patients diagnosed with schizophrenia compared to the healthy population. Finally, in Tada et al 1986 study no significant differences in copper (Cu) concentration was found between patients with schizophrenia and healthy control.…”
Section: Discussionmentioning
confidence: 74%
“…Score plot of the 1 st BE and BPRS canonical variates; dotted line represents the moving median with 5 rows step Our finding of negative correlation of copper (Cu) concentration with total BPRS and negative symptoms was in line with the findings of Wang 1988, Zhai 1990, Luo 1991. It was different to Rahman et al 2009 andConnemann et al 2010 finding that the concentration of copper (Cu) is increased in patients diagnosed with schizophrenia compared to the healthy population. Finally, in Tada et al 1986 study no significant differences in copper (Cu) concentration was found between patients with schizophrenia and healthy control.…”
Section: Discussionmentioning
confidence: 74%
“…Wenn dieser Einbau gestört ist, entsteht ein wenig stabiles Apoprotein. Aufgrund der unterschiedlichen Halbwertszeiten dieser beiden Fraktionen stellt sich im Serum ein Konzentrationsverhältnis von etwa zehn zu eins (Coeruloplasmin:Apocoeruloplasmin) ein, sodass das Gesamtcoeruloplasmin im Serum normalerweise vorwiegend von der hepatischen Kupferreserve abhängt (5).…”
unclassified